The Influence of Entrepreneurial Literacy and Risk Perception on Entrepreneurial Interest in Management Study Program Students (Case Study at Open University) - Anfas, Anfas; Hendrian; Safitri, Julia (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2024)
This study is a quantitative study that tests the influence of independent variables, namely Entrepreneurial Literacy (X1) and Risk Perception (X2) on Entrepreneurial Interest (Y) as the dependent variable. The population in this study were students of the Management Study Program of the Open University (Universitas Terbuka/UT) who were in the Distance Learning Program Unit (Unit Program Belajar Jarak Jauh/UPBJJ-UT) Kendari, with a research sample of 50 respondents. The analysis tool used in this study was Multiple Linear Regression. The results of the study concluded that: (1) Entrepreneurial literacy partially does not have a significant influence on entrepreneurial interest in students of the Management Study Program of the Open University (UPBJJ-UT) Kendari; (2) Risk perception partially does not have a significant influence on entrepreneurial interest in students of the Management Study Program of the Open University (UPBJJ-UT) Kendari; and (3) Entrepreneurial literacy and risk perception simultaneously have an influence on entrepreneurial interest in students of the Management Study Program of the Open University (UPBJJ-UT) Kendari.